Lost in Translation: Early Digital English Exposure and the Delay of Bahasa Indonesia Acquisition in Young Learners - Novalia Tanasy; Suci Ayu Kurniah P; Nurul Fachrunnisa (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This study explores how exposure to English-language digital media influences the functional development of Indonesian as a first language (L1) among early childhood learners. In today's digital era, children are increasingly exposed to English through television shows, online games, and educational apps, often without adequate parental mediation. Using a qualitative descriptive approach, this study involved 20 children aged 5–12 years and their 20 parents in South Sulawesi, Indonesia. Data were collected through observation and interviews to investigate language use tendencies, interaction patterns, and influencing factors. The findings indicate that children with high English media exposure tend to use English more frequently in daily interactions and may demonstrate limited use of Indonesian in specific contexts. This imbalance is influenced by the duration of gadget use, the dominance of English content, and the lack of consistent parental involvement. While not pathologizing bilingualism, the study highlights the need for balanced language exposure to support children’s linguistic and social development. The results offer practical insights for parents, educators, and policymakers to foster additive bilingualism through more intentional and contextually appropriate language learning strategies.